2020
DOI: 10.1108/jiabr-11-2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing socio-economic justice and financial inclusion in Nigeria

Abstract: Purpose The purpose of this paper is to discuss the roles of Zakat, Sadaqah and Qardhul Hassan within the context of the existing literature as major Islamic financial instruments for enhancing socio-economic justice amongst Muslims haves and have-nots as these enhance financial inclusion in Nigeria. Design/methodology/approach The discussion in this paper is based on secondary sources such as the divine knowledge contained in the Qur’an, Hadiths and the existing literature, such as previously conducted empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 40 publications
5
65
0
2
Order By: Relevance
“…We also revealed the most relevant authors in this field as shown in Figure 4. Based on our results, Saad Raj (Saad et al, 2020;Saad and Farouk, 2019) is the most relevant author as he has published 15 relevant articles, followed by Johari F. with 7 articles (Ahmed et al, 2017;Ali et al, 2015) and Sawandi N. with 6 articles (Zauro et al, 2020).…”
Section: General Information and Performance Analysismentioning
confidence: 67%
See 1 more Smart Citation
“…We also revealed the most relevant authors in this field as shown in Figure 4. Based on our results, Saad Raj (Saad et al, 2020;Saad and Farouk, 2019) is the most relevant author as he has published 15 relevant articles, followed by Johari F. with 7 articles (Ahmed et al, 2017;Ali et al, 2015) and Sawandi N. with 6 articles (Zauro et al, 2020).…”
Section: General Information and Performance Analysismentioning
confidence: 67%
“…The definition of zakat indicates also on how an individual can be cleaned and purified from his wealth dirt by the payment of zakat. Additionally, based on the definitions given, virtually all eligible Muslims are required to pay Zakat to the eight Asnaf (who are eligible to receive zakat) to uplift the standard of living of the poor among Muslims (Zauro et al, 2020;Alaro and Alalubosa, 2019;Ahmed and Salleh, 2016).…”
Section: Literature Review 21 Definition Of Zakatmentioning
confidence: 99%
“…That financial inclusion can be addressed either by promoting risk-sharing contracts or through the use of specific instruments of redistribution of wealth among the members of the society (Askari et al, 2010;Iqbal and Mirakhor, 2013). Both risk-sharing financing instruments and redistributive instruments such as Zakat, Sadaqah and Qardhul Hassan complement each other to offer a comprehensive approach to poverty eradication and enhance access to finance among the vulnerable poor especially Muslims communities in Nigeria and ultimately build a healthy and vibrant economy (Gelbard et al, 2014;Zauro et al, 2020). The people affected by the problems of financial exclusion are usually individuals and social groups at the bottom of the social ladder, due to their poor economic conditions such as low income and perhaps lack of financial literacy ( Conkov a et al, 2013).…”
Section: Islamic Perspective On Financial Inclusionmentioning
confidence: 99%
“…Penelitiannya juga menemukan bahwa peran Baitul Maal mengurangi angka kemiskinan. Penelitian (Zauro, Zauro, Saad, & Sawandi, 2020) (Ismail, 2013). Berdasar dari pengertian ini dapat diartikan bahwa dengan pembiayaan qardhul hasan maka usaha kecil akan berkembang dan sekaligus mewujudkan pembangunan ekonomi.…”
Section: Pendahuluanunclassified